KELAYAKAN MASKER WORTEL (Daucus carota L) UNTUK PERAWATAN KULIT WAJAH KERING - Rilli Putri; Rahmiati Rahmiati (Jurnal Tata Rias dan Kecantikan, 2022)
One easy and practical way to overcome this is by doing cosmetic treatments using a face mask with carrots. This study aims to a) To analyze how to make carrot mask (Daucus carota L) for dry facial skin care b) the appropriateness of carrot mask (Daucus carota L) in terms of the content of vitamins C and B1. c) the appropriateness of the carrot mask (Daucus carota L) in terms of aroma, texture, and adhesion (organoleptic test, d) appropriateness of carrot mask (Daucus carota L). This type of research is experimental. Place and time of research conducted in the Laboratory of make-up and beauty Education Study Program. Faculty of Tourism and Hospitality, Padang State University. The object of research is that carrots (Daucus carota L) are made into natural mask powders for dry facial skin care, and the organoleptic properties of traditional carrot masks (Daucus carota L) include aroma, texture, and stickiness as well as panelists' preferences (hedonic). Sources of data are observation, documentation, and questionnaires. Panelists were 7 people. Descriptive data analysis technique by displaying statistics and frequency. Based on the research results, it was found that the content of Vitamin C and Vitamin B1. Vitamin C in the carrot mask (Daucus carota L) is 4.21% and Vitamin B1 in the carrot mask (Daucus carota L) is 7.73. The most organoleptic aroma test, which was 57% said that the aroma was typical of carrots, the texture of 42.5%, the texture of carrots was less smooth and 72% of panelists said that the carrots were quite sticky. Hedonic test 57% of panelists said they liked the carrot mask. Conclusion Carrots contain vitamins C and B1. The organoleptic test was assessed by the distinctive aroma of carrots, the texture was less smooth and quite sticky and the panelists liked the carrot mask